PENGARUH PENGGUNAAN GADGET TERHADAP POLA KOMUNIKASI DALAM KELUARGA - hayati, Nur; Elmanora; Muhammad Faesal (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effect of gadget use on communication patterns in the family. The population of this study was high school students in East Jakarta with a sample of 100 people. The data used by researchers is data obtained through closed questionnaires/surveys for both variables using purposive sampling. In the gadget use variable, there are 28 statements covering aspects of cell phones/cellular phones, television, video games, and internet/computers, while the family communication pattern variable has 19 statements covering aspects of conversation orientation and conformity orientation. Data analysis techniques use descriptive statistics and inferential statistics. The results showed that 55% of high school students using gadgets were in the moderate category. Meanwhile, 52% of high school students have moderate communication patterns. The results showed that gadget use has a significant effect on communication patterns in the family (= -0.355). The higher the use of gadgets can reduce communication patterns in the family. Thus, students need to control the use of gadgets